Activation of the Endothelin System Mediates Pathological Angiogenesis during Ischemic Retinopathy - Patel, Chintan (American Society for Investigative Pathology, 2014)
Retinopathy of prematurity adversely affects premature infants because of oxygen-induced damage of the immature retinal vasculature, resulting in pathological neovascularization (NV). Our pilot studies using the mouse model of oxygen-induced retinopathy (OIR) showed marked increases in angiogenic mediators, including endothelins and endothelin receptor (EDNR) A. We hypothesized that activation of the endothelin system via EDNRA plays a causal role in pathological angiogenesis and up-regulation of angiogenic mediators, including vascular endothelial growth factor A (VEGFA) in OIR. Mice were exposed to 75% oxygen from post-natal day P7 to P12, treated with either vehicle or EDNRA antagonist BQ-123 or EDNRB antagonist BQ-788 on P12, and kept at room air from P12 to P17 (ischemic phase). RT-PCR analysis revealed increased levels of EDN2 and EDNRA mRNA, and Western blot analysis revealed increased EDN2 expression during the ischemic phase. EDNRA inhibition significantly increased vessel sprouting, resulting in enhanced physiological angiogenesis and decreased pathological NV, whereas EDNRB inhibition modestly improved vascular repair. OIR triggered significant increases in VEGFA protein and mRNA for delta-like ligand 4, apelin, angiopoietin-2, and monocyte chemoattractant protein-1. BQ-123 treatment significantly reduced these alterations. EDN2 expression was localized to retinal glia and pathological NV tufts of the OIR retinas. EDN2 also induced VEGFA protein expression in cultured astrocytes. In conclusion, inhibition of the EDNRA during OIR suppresses pathological NV and promotes physiological angiogenesis.